STUDI TENTANG KATEGORISASI PENGEMIS DIKOTA PEKANBARU - Puji Lestari; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This reseach was conducted in the pekanbaru city, as the research objek or beggars in the city of Pekanbaru. The purpose of the study was to determine the kategoritation of beggars end the factor that make them become begars.the subjek of this research is a beggar who was found earlier by author, this research was conducted in the moon of september 2014, while the study was conducted in a beggar while opperating as Kodim Market, Ramayana, the Mal Pekanbaru and place of residence.from the research found that the factor causing them to become beggars of them all feeling lazy, low education, physical dissability, lack of understanding of religion, ald age and environment.Keywords : begars, poverty, behaviour